Awareness and Myths Related to COVID-19 among Medical Students at a Tertiary Health Care Facility in Northern India. - NILIMA Takhelchangbam; Naresh Pal Singh; Anamika Singh; Deepanshi Saxena; Prashant Kumar Bajpai; Utkarsh Tripathi; Arushi Kumar (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Assessing the undergraduate medical students' knowledge regarding COVID-19 to determine any gaps in their learning and any misinformation is essential. This study aimed to access the awareness regarding COVID-19 and related myths among undergraduate medical students. Methodology: A cross-sectional survey was conducted on undergraduate medical students in a tertiary healthcare teaching institute in a district of central Uttar Pradesh. Unpaired t-test and one-way ANOVA were applied to determine any differences among the mean scores of awareness and myths among gender and batch years. We used boxplots to represent the overall and section-wise correct percentages. Results: Out of the total 800 students, 494 (61.7%) participated in the study. Most of the participants were first-year MBBS students, 158 (32.0%), and were males (280, 56.7%). The average performance regarding the awareness and myth related to COVID-19 was satisfactory, with a 72.5% overall correct mean score. According to modified Bloom's cut-off, 406 (82.2%) students performed moderately, followed by 81 (16.4%) students who performed good, and seven (1.4%) performed poorly. Although the majority 489 (99.0%) knew the correct taxonomy of the virus causing COVID-19, 60.0% and 43.0% had difficulty defining the SARS-CoV-2 virus and close contacts, respectively. There was a drastic variation in response to the physical distancing criteria, with only 71 (14.4 %) answered correctly. Conclusions: As the guidelines regarding COVID-19 are dynamic, there is a need for regular training of undergraduate medical students, focusing on infection control and prevention to keep them updated with the latest and upcoming guidelines.